Efficacy and Safety of Endoscopic Anti-Reflux Therapy versus Sham or Proton Pump Inhibitor Control in Gastro-oesophageal Reflux Disease: A Meta-Analysis of Randomised Controlled Trials - Tiffano Taufan Firdaus; Vesri Yoga (Phlox Institute: Indonesian Medical Research Organization, 2026)
Background: Gastro-oesophageal reflux disease (GERD) is among the most prevalent chronic disorders, and lifelong proton pump inhibitor (PPI) dependence is common. Endoscopic anti-reflux therapies are minimally invasive alternatives between medical and surgical management, but individual device trials are small and the randomised evidence has largely been synthesised device by device. Objective: To pool the randomised evidence across all endoscopic anti-reflux modalities against a common control and provide a single, class-level estimate of benefit in adults with GERD. Methods: Four databases were searched for randomised controlled trials comparing endoscopic anti-reflux therapy (radiofrequency, suturing/plication, injection/implant, transoral incisionless fundoplication) with a sham procedure and/or continued PPI in adults with GERD. Risk ratios (RR) for treatment success were pooled with a DerSimonian–Laird random-effects model; heterogeneity was quantified with I² and a prediction interval; bias was appraised with Cochrane RoB 2.0. Results: Twelve trials were eligible; seven were pooled (536 participants; follow-up 3–6 months). Endoscopic anti-reflux therapy approximately doubled treatment success versus sham or PPI control (pooled RR 1.89, 95% CI 1.51–2.37; p<0.001; I² 23.6%; prediction interval 1.17–3.05) — about 28 percentage points absolute, NNT ≈4. The effect persisted across subgroup, low-risk-of-bias, current-device and leave-one-out analyses; a secondary PPI reduction/cessation analysis confirmed benefit (RR 1.82, 95% CI 1.43–2.30; I² 0%). Serious adverse events were infrequent, concentrated among injection/implant devices. Conclusion: In adults with GERD, endoscopic anti-reflux therapy produced a clinically meaningful, robust improvement in short-to-intermediate-term treatment success versus sham or continued PPI, consistently across device classes; durability and device-specific safety require ongoing evaluation.